Spatiotemporal processes of plant phenology : simulation and prediction - Chen, Xiaoqiu (Springer, 2017)
This book deals with phenology, the study of recurring biological life cycle stages, and especially their timing and relationships with biotic and abiotic forces. Given the theoretical and methodological innovations involved, the chapters on defining spatiotemporal patterns of plant phenology and constructing daily temperature-based temporal/spatial models and process-based regional unified models will be of particular interest. Helping readers discover and explore plant phenology's perspectives in terms of spatiotemporal patterns, processes and mechanisms, the book will also equip young scientists and graduate students to understand the causes of spatiotemporal variation in vegetation seasonality.
Keywords: Plant phenology.; Plant phenology -- Remote sensing.; Plant phenology -- Computer simulation.; elektronické knihy; electronic books